Mental health, attachment and breastfeeding: implications for adopted children and their mothers - Gribble Karleen D (BMC, 2006)
Abstract Breastfeeding an adopted child has previously been discussed as something that is nice to do but without potential for significant benefit. This paper reviews the evidence in physiological and behavioural research, that breastfeeding can play a significant role in developing the attachment relationship between child and mother. As illustrated in the case studies presented, in instances of adoption and particularly where the child has experienced abuse or neglect, the impact of breastfeeding can be considerable. Breastfeeding may assist attachment development via the provision of regular intimate interaction between mother and child; the calming, relaxing and analgesic impact of breastfeeding on children; and the stress relieving and maternal sensitivity promoting influence of breastfeeding on mothers. The impact of breastfeeding as observed in cases of adoption has applicability to all breastfeeding situations, but may be especially relevant to other at risk dyads, such as those families with a history of intergenerational relationship trauma; this deserves further investigation.